Plataforma educaplay y su aporte en el refuerzo académico de los estudiantes de tercer año de bachillerato de la Unidad Educativa José Maria Estrada Coello, del cantón Babahoyo, Provincia Los Ríos - Rizzo Montiel, Kleber Bayron (2019)
The present research work arose as a need to implement technological, didactic, interactive tools that help to obtain and share a large amount of information as well as learn interactively through activities offered by the Educaplay platform, which if used with the pedagogical guide of the teachers will contribute to the academic reinforcement of the third year students of the baccalaureate of the Educational Unit "José María Estrada Coello", managing to awaken the interest of the student by the new information and communication technologies that will allow them to be updated with these new resources technologies and integrate the current information society. In the educational field, the use of ICT should not be limited to transmitting only knowledge, even if it is necessary; In addition, it should seek to train in certain skills the need to train in a healthy critical attitude towards ICT. With this, we mean to know how to distinguish what help us and what limit us, to be able to act accordingly. This process must be present and given in an integrated manner in the family, at school and in society The results obtained by the survey of students and teachers concluded that with the help of a didactic guide on information and communication technologies, especially on the Educaplay platform, teachers will be trained on the innovative technological resources provided by the web, which allows generating new methodologies for teaching-learning by improving their academic performance, as well as being an interactive form of academic reinforcement for the various activities it offers to learn in an autonomous way that is to say it obtains learning through experiences generated by the platform.